Investigation of loosely and firmly bound albumin and lysozyme layers on dental materials. Issue 6 (25th April 2016) - Kratz, Fabian; Trautmann, Simone; Umanskaya, Natalia; Müller‐Renno, Christine; Hannig, Matthias; Ziegler, Christiane
Abstract : The total amount of albumin and lysozyme adsorbed on different dentally relevant materials like titanium, gold, ceramics, poly(methyl methacrylate) (PMMA) and polytetrafluoroethylene (PTFE) was measured by bicinchoninic acid assay (BCA assay) after detachment of the proteins from the samples. The total amount of protein was separated into the amount of loosely and firmly adsorbed protein. The parts of loosely and firmly bound protein differ remarkably depending on the material. For albumin, the loosely bound protein dominates the total adsorption. In contrast, for lysozyme the amount of loosely and firmly bound protein is in some cases equal and sometimes there is more firmly than loosely bound lysozyme. In general, the firmly bound protein masks the electrostatics of the surface. The amount of loosely bound protein follows no strict tendency, whereas the amount of firmly bound protein is mostly governed by entropic and hydrophobic interactions, but modulated by electrostatics and thus by the isoelectric points of the surface and of the proteins. Most protein adsorbs on the metallic surfaces, if compared to the investigated non‐metallic surfaces. For the adsorption on gold, the number of cysteines in the amino acid sequence influences the amount of protein on the gold surface. Least albumin adsorbs on PMMA, least lysozyme adsorbs on PMMA and PTFE. For albumin, pH depending conformational changes play a key role for the adsorption at pH 9.0.